Woman-to-woman: Feasibility of a lay health advisor program for cervical cancer education in Grenada, W.I. - Kamilah B. Thomas-Purcell; Samantha Patterson; Andrew N. McIntosh; Christine Richards; Marva Primus-Joseph; Donrie J. Purcell; Kimlin Ashing (Elsevier, 2022)
Objective: The aim of this study was to evaluate the impact of Woman- to-Woman, a lay health advisor (LHA)-led educational intervention on cervical cancer and human papillomavirus (HPV) knowledge in a cohort of at-risk Grenadian women. Methods: LHAs from high-risk parishes were trained in the administration of the intervention and administered the program to 78 local women. Participants completed a pre- and post-knowledge test and a session evaluation. LHAs participated in a process evaluation focus group. Results: Sixty-eight percent (68%) of participants obtained higher knowledge scores following the educational intervention. The difference between the pre- and post-test scores was statistically significant (p = 0.05). Almost 94% agreed that they were taught new and useful information by credible, community informed and responsive LHAs. Ninety percent (90%) indicated great satisfaction and high motivation to recommend to others. LHAs reported on the intervention and their community interactions. Conclusions: Results demonstrate that a LHA-led educational intervention significantly improved participants' knowledge of cervical cancer, HPV, Papanicolaou test and vaccination against HPV. Innovations: Researchers trancreated an evidenced based intervention originally designed for Latina women for Grenadian women. There is no evidence in the literature of previous LHA- cervical cancer education studies conducted in Grenada nor the Caribbean.